2005
DOI: 10.1097/01.ico.0000138837.52694.37
|View full text |Cite
|
Sign up to set email alerts
|

Surface Pressure Measurements of Human Tears and Individual Tear Film Components Indicate That Proteins Are Major Contributors to the Surface Pressure

Abstract: Comparison between the dynamic Pi-A profiles of tears and those of individual tear film components shows that tear film proteins not only are capable of surface activity but also are major contributors to the surface activity of the tear film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 42 publications
6
51
2
1
Order By: Relevance
“…1. The isotherms of the three "pure" compounds, MGS, SM and DPPC coincide well with the previously published results obtained under similar conditions [18][19][20]29,34]. MGS isotherm shows low slope (i.e.…”
Section: Quasi-equilibrium Compression Of Mixed Films Of Mgs and Plssupporting
confidence: 90%
See 2 more Smart Citations
“…1. The isotherms of the three "pure" compounds, MGS, SM and DPPC coincide well with the previously published results obtained under similar conditions [18][19][20]29,34]. MGS isotherm shows low slope (i.e.…”
Section: Quasi-equilibrium Compression Of Mixed Films Of Mgs and Plssupporting
confidence: 90%
“…MGS isotherm shows low slope (i.e. high compressibility) with characteristic inflexion at 15-17 mN and maximal surface pressure of 25 mN/m as reported in [18][19][20].…”
Section: Quasi-equilibrium Compression Of Mixed Films Of Mgs and Plsmentioning
confidence: 57%
See 1 more Smart Citation
“…The present conceptual study clearly illustrates the potential effect of PLs without considering interactions between lipids and proteins. The function of PLs may be highly affected by lipid-binding proteins such as lipocalin, [24][25][26] and PL transfer protein. 27,28 However, more investigations need to be performed regarding the lipid-protein interactions before the impact of the proteins on TFLL behavior can be explained in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, apart from the bactericidal role, Tragoulias et al (2005) and Millar et al (2006) have suggested that lysozyme contributes to lower the surface tension of the tear fi lm. In this case, an increase in lysozyme levels could contribute to stablizing the tear fi lm, thus avoiding an excessive evaporation and the resulting problems on the ocular surface.…”
Section: Discussionmentioning
confidence: 99%